Gardnerella vaginalis infection in pregnancy: Effects on placental development and neonatal outcomes. (24th March 2022) - Wong, Yin Ping; Cheah, Fook Choe; Wong, Kon Ken; Shah, Shamsul Azhar; Phon, Su Ee; Ng, Beng Kwang; Lim, Pei Shan; Khong, Teck Yee; Tan, Geok Chin
Abstract: Introduction: Gardnerella vaginalis (GV)-associated bacterial vaginosis is recognised for its detrimental effects on pregnancy resulting in poor obstetric and neonatal outcomes. There is limited knowledge of the effects on placental histomorphology following GV infection in pregnancy. We investigated the effects of GV infection on the placenta, particularly with regards to the syncytiotrophoblasts and vascular development, and related these to neonatal outcomes. Methods: A prospective cohort study involving GV-positive pregnant women presented with abnormal vaginal discharge, with gestational age-matched healthy pregnant women controls. Placental sampling was performed upon delivery and examined histologically. Vascular endothelial growth factor-A (VEGF-A) and hypoxia-inducible factor-1α (HIF-1α) mRNA and protein expression were analysed by real-time PCR and immunohistochemistry respectively. The standard measures in neonatal outcomes were recorded. Results: Placentas from GV-positive mothers were found to have significant histological evidence of maternal and/or fetal inflammatory response compared with the controls (17/28: 60.7% vs 2/20: 10%) (p = 0.0011). There was an increase in the percentage of syncytial nuclear aggregates (SNAs) per villus (47.4 ± 11.09%) in placentas from GV-positive mothers (p < 0.0001). VEGF-A was significantly increased in specifically, the villous endothelial cells of placentas with GV infection, but no difference in the immunoexpression of HIF-1α in these cells between groups. However, these were not associated with adverse neonatal outcomes. Discussion: Increased placental VEGF-A expression associated with increased SNAs in pregnant women with GV infection of the genital tract may be an intrauterine response towards placental vascular remodeling, that may also serve as a protective role in moderating birth outcomes. Highlights: Maternal Gardnerella vaginalis infection is associated with placental inflammation. Placental vascular alteration is evident in maternal Gardenerella vaginalis infection. Such vascular alteration may serve a protective role in moderating birth outcomes.